(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Soybean (_Glycine max_ L.) and cotton (_Gossypium hirsutum_ L.) are two important crops worldwide. Understanding the influence of physical and chemical factors on these species is crucial for optimizing crop growth, yield, and quality. This study investigated the effects of temperature, water, light, soil, nutrients, and other factors on the growth and development of soybean and cotton. The results provide valuable insights for crop management and improvement.